Evaluation of apical crack formation associated with root canal preparation with ProTaper Next, ProTaper Gold, and TruNatomy systems - N Neslihan Yilmaz Çirakoglu; Yağız Özbay (Wolters Kluwer Medknow Publications, 2021)
Aim: The present study aimed to evaluate and compare the microcrack formation in apical root dentin as a result of root canal preparation with different nickel-titanium (NiTi) rotary systems. Materials and Methods: Sixty extracted mandibular premolar teeth with single canals were used. Apical 1 mm of roots was flattened perpendicular to the tooth axis. Forty-five teeth were prepared using ProTaper Next (PTN), ProTaper Gold (PTG), or TruNatomy files. Fifteen teeth were left unprepared as the negative control group. Images of apical surfaces of roots were obtained using a stereomicroscope at × 20 magnification. The presence of microcracks was noted with the help of the images. The data were analyzed with a Chi-square test using MiniTab 17 Statistical Software. Results: There was a statistically significant difference between the PTN and TruNatomy groups (P < 0.05). There was no statistically significant difference between the PTG group and other groups (P > 0.05). Conclusion: Whereas all rotary files created microcracks in the apical root dentin, TRN caused fewer microcracks than other NiTi rotary systems.